TME-targeted approaches of brain metastases and its clinical therapeutic evidence - Khan, Ibrar Muhammad; Khan, Safir Ullah; Sala, Hari Siva Sai; Khan, Munir Ullah; Ud Din, Muhammad Azhar; Khan, Samiullah; Hassan, Syed Shams ul; Khan, Nazir Muhammad; Liu, Yong (Frontiers in Immunology, 2023)
The tumor microenvironment (TME), which includes both cellular and non-cellular elements, is now recognized as one of the major regulators of the development of primary tumors, the metastasis of which occurs to specific organs, and the response to therapy. Immunotherapy and targeting have increased knowledge of cancer-related inflammation. The brain is a remarkable and highly developed organ in this regard. Since the blood-brain barrier (BBB) and blood-cerebrospinal fluid barrier (BCB) prevent immune cells from entering from the periphery, it has long been considered an immunological refuge. Thus, tumor cells that make their way to the brain are believed to be protected from the body's normal mechanisms of monitoring and eliminating them. In this process, the microenvironment and tumor cells at different stages interact and depend on each other to form the basis of the evolution of tumor brain metastases. This paper focuses on the pathogenesis, microenvironmental changes, and new treatment methods of different types of brain metastases. Through the systematic review and summary from macro to micro, the occurrence and development rules and key driving factors of the disease are revealed, and the clinical precision medicine of brain metastases is comprehensively promoted. Recent research has shed light on the potential of TME-targeted and potential treatments for treating Brain metastases, and we'll use that knowledge to discuss the advantages and disadvantages of these approaches.